2021
DOI: 10.1097/gox.0000000000003172
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Tranexamic Acid in Plastic Surgery: What’s New?

Abstract: Background: Blood loss associated with surgical interventions can lead to several complications. Therefore, minimizing perioperative bleeding is critical to improve overall survival. Several interventions have been found to successfully reduce surgical bleeding, including the antifibrinolytic agent. After aprotinin was withdrawn from the market in 2008, TXA remained the most commonly used medication. The safety and efficacy of TXA has been well studied in other specialties. TXA has been rarely use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 89 publications
1
53
0
1
Order By: Relevance
“…TXA inhibits fibrinolysis by attaching to the lysine-binding site of plasminogen and preventing its conversion to plasmin, thereby reducing degradation of blood clots. It can also prevent plasmin-led degradation of platelet receptors, thus preserving platelet function 11 . There is limited high-level clinical guidance as to the effects of administering TXA in patients with acute MI, given the experiences that led to the clinical withdrawal of aprotinin 1,12,13 .…”
Section: Discussionmentioning
confidence: 99%
“…TXA inhibits fibrinolysis by attaching to the lysine-binding site of plasminogen and preventing its conversion to plasmin, thereby reducing degradation of blood clots. It can also prevent plasmin-led degradation of platelet receptors, thus preserving platelet function 11 . There is limited high-level clinical guidance as to the effects of administering TXA in patients with acute MI, given the experiences that led to the clinical withdrawal of aprotinin 1,12,13 .…”
Section: Discussionmentioning
confidence: 99%
“…In the same vein, Lee et al performed an SR study (13 articles with a sample size of 2271 cases) and indicated that TXA could reduce continued bleeding, mortality, and urgent endoscopic intervention (35), which is consistent with the results of this study. TXA is a cheap and affordable medicine that can reduce the rate of hemorrhage and, consequently, the accessibility and need for blood, which has been shown to be effective in a variety of surgeries, including spine, obstetrics, plastic, and chest surgery (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…2 Tranexamic acid (TXA) is a synthetic amino acid that inhibits fibrinolysis. 3,4 It has been shown to reduce blood loss and the need for blood transfusion in trauma, elective total knee arthroplasty, dental extractions, spine surgery, and cardiac surgery. [5][6][7][8][9] Topical tranexamic acid has been used for treatment of postoperative bleeding in anticoagulated patients after oral and cardiac surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have reported efficacy and safety when used preoperatively and intraoperatively in various plastic surgery procedures. 3,4 Despite a substantial rise in the use of tranexamic acid in plastic surgery procedures, there is a paucity of literature examining the effectiveness of tranexamic acid in craniofacial surgery and particularly in pediatric and orthognathic patients. 13 The purpose of this FACE 3 (1) systematic review was to review the current literature as it pertains to the effectiveness of tranexamic acid administration in pediatric craniofacial and orthognathic surgery.…”
Section: Introductionmentioning
confidence: 99%